Stool and vaginal microbiome profiles patterns among Black and White endometrial cancer survivors: A pilot study in North Carolina - Mu Jin; Temitope Keku; Amber McCoy; Jordyn A. Brown; Marc Peterson; Jamie Hunter; Shawn Smith; Stephenie Black-Grant; Melinda S. Yates; Anne F. Peery; Victoria L. Bae-Jump; M. Andrea Azcarate-Peril; et al. (PLoS ONE, 2026)
Background Endometrial cancer is the most common gynecologic cancer in the US. Endometrial cancer survivors may experience changes in microbiome due to cancer treatment and other factors. The human microbiome plays a crucial role in maintaining the proper functioning of the body. A more diverse microbiome often indicates a healthier gut environment, while lower vaginal microbiome diversity, specifically a Lactobacillus -dominant vagitype, is associated with more favorable health outcomes. The objectives of this pilot study were to evaluate potential variation in stool and vaginal microbiome communities and to assess the feasibility and acceptability of self-sampling among endometrial cancer survivors. Methods Endometrial cancer survivors (N = 50) enrolled in the Carolina Endometrial Cancer Study, a cohort of women diagnosed with endometrial cancer, were mailed Genotek vaginal swab and stool self-collection kits. Self-reported questionnaires assessed information on survivors’ demographics, sexual and bowel function, and perspectives on the self-sampling processes. Tumor characteristics and cancer treatment information were assessed from medical records. Microbiota profiles were characterized by bacteria 16S rRNA amplicon sequencing. Results Overall, 48 vaginal swabs and 47 stool samples were obtained. Alpha (Shannon p = 0.04) and beta (Bray-Curtis p = 0.004) diversity of vaginal microbiome samples varied by cancer treatment, with higher microbial diversity after chemotherapy or radiation compared to surgery alone. In the surgery only group, 63% of samples were Lactobacillus -dominant compared to 17% among the chemotherapy or radiation group. Stool microbiome diversity did not vary by cancer treatment status. No statistically significant differences in alpha or beta diversity were observed in either vaginal or stool microbiome communities across racial subgroups or by sexual or bowel function. Conclusion Self-collection of stool and vaginal microbiome samples is feasible and acceptable in cancer survivors. Our results suggest that radiation and chemotherapy for endometrial cancer may decrease the abundance of beneficial Lactobacillus and increase less favorable vaginal microbial diversity among endometrial cancer survivors.